Studi Kasus Penerapan Continuous Review Sistem (Q) dalam Manajemen Persediaan untuk Optimalisasi Biaya Produksi di UD. Indokarya Brass - Wendra Ananda Faudjie; Muhammad Sagaf (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
UD. Indokarya Brass is a company engaged in the brass handicraft industry with its main products being door handles and bells. The main raw materials used in the production process include brass, copper, tin, and aluminum, which are obtained from suppliers both within and outside the city. On average, raw materials are received weekly with quantities of 50–100 kg of brass, 7–10 kg of copper, 10–15 kg of tin, and 3–5 kg of aluminum. In addition, the company also uses additional materials in the form of thinner and epoxy purchased from nearby hardware stores with less frequent purchases, namely 5–10 liters of thinner every month and around 5 kg of epoxy every two months. To date, the company has not had a structured policy for procurement and control of raw material inventory. This condition results in excess inventory of several types of raw materials which actually incurs high costs, both in terms of storage costs and warehouse maintenance costs. This excess inventory ultimately has an impact on reduced efficiency and decreased company profits. This study was conducted to analyze the existing inventory system and compare the company's current policy with a proposed method for more optimal inventory control. The calculation results show that the proposed method is able to provide significant inventory cost savings, namely 83.25% in brass raw materials, 15.28% in copper, 14.6% in tin, 43.37% in aluminum, 4.66% in epoxy, 4.2% in thinner, and 40.7% in other raw materials. Thus, the implementation of the right inventory control method can improve operational efficiency and help companies reduce cost burdens, so that profits can be more optimal.